Tracheal Complications Following Prolonged Invasive Ventilation in Tracheostomized Pediatric Patients with Complex Chronic Conditions - Dejan Vlajnic; Deborah Wiesmann; Jens Ortmann; Mandira Reuther; Boris Zernikow (Children, 2025)
This case series presents four pediatric patients who developed tracheal complications after prolonged invasive mechanical ventilation. The first case involved an 11-year-old girl with severe hypoxic encephalopathy who developed extensive ulcerative granulation tissue obstructing 60% of the tracheal lumen. The second case was that of a 6-year-old boy with ACTA1-related nemaline myopathy who experienced recurrent tracheal obstruction due to granulomatous tissue formation. The third case involved a 9-year-old boy with hydroxyglutaric aciduria and a large plug obstructing his trachea. The last case involved a 19-year-old female with lissencephaly who developed a tracheoesophageal fistula. These cases highlight the importance of regular surveillance and early intervention in managing tracheal complications in pediatric patients with complex chronic conditions requiring long-term mechanical ventilation. The authors emphasize the need for specialized care and routine endoscopic examinations in order to prevent and address potentially life-threatening complications in this vulnerable patient population.